The multiple intelligences of reading and writing : making the words come alive - Armstrong, Thomas (Association for Supervision and Curriculum Development, 2003)
The author of the bestselling book Multiple Intelligences in the Classroom offers practical strategies for teaching reading and writing through multiple intelligences.